Differential field response of two Mediterranean tree species to inputs of sewage sludge at the seedling stage - Valdecantos, Alejandro; Cortina, Jordi; Vallejo, V Ramón (Ecological Engineering, 2011)
Land degradation and desertiﬁcation is a common feature in Mediterranean landscapes due to extensive and intensive land use and natural orman induced disturbances. The ecosystemmay need external inputs to recover its composition and function as soils are often impoverished and vegetal key stone species lost. We evaluated the effects of the application of fresh and air-dried biosolids in the establishment and morphological and physiological performance of seedlings of Pinus halepensis and Quercus ilex under dry Mediterranean ﬁeld conditions. Seedling survival was not affected by biosolid treatments in any of the studied species both two and ten years after planting. During the ﬁrst two years, growth was enhanced by the two biosolid treatments in relation to control, although the change in the biomass allocation pattern differed between species. Rooting depthwas signiﬁcantly enhanced by liquid biosolid in Q. ilex and marginally reduced in P. halepensis as well as the exploration of soil. As a consequence, root-to-shoot ratio reduced signiﬁcantly with dry and liquid sludge due to promoted aboveground growth whilemaintaining and even reducing belowground fractions.An improvement ofthe nutritional status, offertilized seedlings especially of phosphorus, is the explanation for the better ﬁeld performance. Vector analysis revealed an important phosphorus limitation for both species that was overcome with the application of liquid (both species) and air-dried biosolid (pine). The higher growth of pine seedlings attained in the liquid biosolid treatment was coupled with a signiﬁcant decrease in foliar 13 C, suggesting lower water use efﬁciency. The signiﬁcant increase in foliar 15 N in the biosolid treatments in both species suggested that a large proportion of the total nitrogen uptake came from the applied biosolids. Instead, with regard to the low biosolid application rate used in the study, treatments had an overall positive effect as a restoration tool by improving nutritional status and promoting growth of planted seedlings.
Keywords: Biomass allocation pattern; Biosolids; Foliar isotopic composition; Pinus halepensis; Quercus ilex; Restoration; Vector diagnose